Severe Cholestasis and Bile Cast Nephropathy Induced by Anabolic Steroids Successfully Treated with Plasma Exchange - Christelle El Khoury; Toni Sabbouh; Hussein Farhat; Antoine Ferzli (Case Reports in Medicine)
We report a case of a bodybuilder who took a regimen of anabolic steroids containing stanozolol and testosterone propionate for 8 weeks which led to the development of jaundice and severe pruritus with serum total bilirubin reaching 41.22 mg/dL. Despite supportive care with fluid and albumin therapy, serum creatinine was progressively increasing. He underwent 6 successful sessions of plasma exchange (PE) with marked improvement at the end of the sessions. Three months after discharge, the patient’s creatinine and total bilirubin levels were 1.08 mg/dL and 1.2 mg/dL, respectively.